Implementasi QR code untuk Memperkenalkan Instrumen Optik - Hanna Nurul Husna; Siti Mita Rofi’atun Zawjiyah; Chita Widia (Postgraduate, University of Mataram, 2023)
The laboratory is one of the important facilities and supports the implementation of learning in tertiary institutions. However, in carrying out practicum activities, students are often constrained by information regarding names, functions, and steps for using instruments. Therefore, the need for information about laboratory equipment is quite important for students. This study aims to produce a website based on a QR code to provide information about the instrument to users and the steps to use it. This research uses research and development methods with the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). The questionnaire is used to measure user responses regarding the QR code and its application. Based on the analysis of the problems found, the QR code was successfully created. This QR code was validated by media experts and instrument content experts and obtained valid results. Users show a positive response regarding the use of the QR code for introducing of Refraction Laboratory instruments. Thus, a website-based QR code can be used to provide optical instrument information to users. However, socialization about its use is very necessary for laboratory users.